2018
DOI: 10.1146/annurev-biochem-062917-012405
|View full text |Cite
|
Sign up to set email alerts
|

Translesion and Repair DNA Polymerases: Diverse Structure and Mechanism

Abstract: The number of DNA polymerases identified in each organism has mushroomed in last two decades. Most newly found DNA polymerases specialize in translesion synthesis and DNA repair instead of replication. Although intrinsic error rates are higher for translesion and repair polymerases than for replicative polymerases, the specialized polymerases increase genome stability and reduce tumorigenesis. Reflecting the numerous types of DNA lesions and variations of broken DNA ends, translesion and repair polymerases dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
206
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(210 citation statements)
references
References 149 publications
2
206
0
2
Order By: Relevance
“…Crystal structures of TLS polymerases have been determined, providing a molecular basis for understanding their biochemical properties (reviewed by Yang and Woodgate. , Yang and Gao, ; Goodman and Woodgate, ).…”
Section: Tls Polymerasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Crystal structures of TLS polymerases have been determined, providing a molecular basis for understanding their biochemical properties (reviewed by Yang and Woodgate. , Yang and Gao, ; Goodman and Woodgate, ).…”
Section: Tls Polymerasesmentioning
confidence: 99%
“…Crystal structures of TLS polymerases have been determined, providing a molecular basis for understanding their biochemical properties (reviewed by Woodgate. 2007, Yang andGao, 2018;Goodman and Woodgate, 2013). All three E. coli TLS polymerases interact with the β-clamp (Hughes et al, 1991;Sutton et al, 1999, Sutton andDuzen, 2006;Bunting et al, 2003;Patoli et al, 2013).…”
Section: Tls Polymerasesmentioning
confidence: 99%
“…The first crystal structures of the TdT polymerase and of binary complexes with either a primer or an incoming triphosphate were resolved in 2002 by Delarue et al . This analysis revealed that the overall structure of the TdT is quite rigid and similar to that of most other polymerases, as it presents the typical thumb, fingers, and palm elements. On the other hand, the presence of an unusual 16 amino acid long loop (called loop 1) adopting a lariat‐like structure is believed to hinder the accommodation of a templating strand and, thus, to account for the template specificity .…”
Section: Terminal Deoxynucleotidyl Transferasementioning
confidence: 99%
“…This modification promotes a switch from the replicative polymerase to specialized low-fidelity polymerases, which contain both PIP-boxes as well as ubiquitin-binding motifs, and thus preferentially bind to ubiquitinated PCNA ( Ubi PCNA) (Bienko et al, 2005;Choe and Moldovan, 2017;Guo et al, 2006;Hoege et al, 2002;Kannouche et al, 2004;Stelter and Ulrich, 2003). These specialized polymerases promote the bypass of replication obstacles in order to maintain efficient DNA-replication, a process known as translesion synthesis (TLS) (Vaisman and Woodgate, 2017;Yang and Gao, 2018).…”
Section: Introductionmentioning
confidence: 99%